Perforation of small intestinal metastasis of lung adenocarcinoma treated with pembrolizumab: a case report - Shoki Sato; Naoto Senmaru; Keita Ishido; Takahiro Saito; Saseem Poudel; Jun Muto; Yasuhito Syouji; Ryunosuke Hase; Satoshi Hirano (Surgical Case Reports)
Abstract Background Pembrolizumab is an immune checkpoint inhibitor and is an anti-human programmed cell death-1 (PD-1) monoclonal antibody. Pembrolizumab is used for non-small cell lung carcinoma with high programmed cell death ligand-1 (PD-L1) expression. It has been found that better overall survival can be obtained using pembrolizumab compared to the existing chemotherapy. We report a case of perforation of small intestinal metastasis after pembrolizumab treatment. Case presentation A 62-year-old man was treated by pembrolizumab for PD-L1 highly expressed lung adenocarcinoma, with multiple metastasis (small intestinal, lymph nodes, and bone). The treatment was stopped owing to drug-induced pneumonitis. One month after drug withdrawal, the patient visited the emergency department of our hospital with the complaint of severe stomachache. He had a rigid abdomen and generalized tenderness, and computed tomography scans showed free air within the abdomen. We diagnosed bowel perforation and performed emergency surgery. Surgical findings revealed multiple small intestine metastasis and mesenteric lymph node metastasis. Perforation was found in the metastatic site in the jejunum located around 40 cm anal to Treitz’s ligament. This perforated part was resected, and functional end-to-end anastomosis was performed using linear staplers. The post-operative course was uneventful. Pathological examination revealed lung adenocarcinoma metastasis at the perforation site, and the effectiveness of pembrolizumab was grade 1b (Japanese Classification of the Colorectal Carcinoma, seventh edition). Conclusions This is the first report of perforation of small intestinal metastasis of lung adenocarcinoma after pembrolizumab treatment. Because pembrolizumab causes some side effects, particularly autoimmune side effects, careful attention during treatment is warranted.